Small GTPase Rap1A/B Is Required for Lymphatic Development and Adrenomedullin-Induced Stabilization of Lymphatic Endothelial Junctions. Issue 10 (October 2018) - Xu, Wenjing; Wittchen, Erika S.; Hoopes, Samantha L.; Stefanini, Lucia; Burridge, Keith; Caron, Kathleen M.
Abstract : Objective—: Maintenance of lymphatic permeability is essential for normal lymphatic function during adulthood, but the precise signaling pathways that control lymphatic junctions during development are not fully elucidated. The Gs -coupled AM (adrenomedullin) signaling pathway is required for embryonic lymphangiogenesis and the maintenance of lymphatic junctions during adulthood. Thus, we sought to elucidate the downstream effectors mediating junctional stabilization in lymphatic endothelial cells. Approach and Results—: We knocked-down both Rap1A and Rap1B isoforms in human neonatal dermal lymphatic cells (human lymphatic endothelial cells) and genetically deleted the mRap1 gene in lymphatic endothelial cells by producing 2 independent, conditional Rap1a/b knockout mouse lines. Rap1A/B knockdown caused disrupted junctional formation with hyperpermeability and impaired AM-induced lymphatic junctional tightening, as well as rescue of histamine-induced junctional disruption. Less than 60% of lymphatic- Rap1a/b knockout embryos survived to E13.5 exhibiting interstitial edema, blood-filled lymphatics, disrupted lymphovenous valves, and defective lymphangiogenesis. Consistently, inducible lymphatic- Rap1a/b deletion in adult animals prevented AM-rescue of histamine-induced lymphatic leakage and dilation. Conclusions—: Rap1 (Ras-related protein) serves as the dominant effector downstream of AM to stabilize lymphatic junctions. Rap1 is required for maintaining lymphatic permeability and driving normal lymphatic development. Abstract : Supplemental Digital Content is available in the text.